The Deviation of Criminal Law Principles in Embezzlement of Joint Property Committed by Husband or Wife - Supriadi, Moh; Husain, Natasya Auliya; Jasri Akadol, Nina Septiana; Gayatri, Nungky Dwi; Yuliana, Yuliana; Natalia, Kristiani (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This study aims to determine the deviation of criminal law principles in the embezzlement of joint assets committed by a husband or wife in marriage. Therefore, criminalization is an ideal policy formulation to overcome this deviation. This study uses normative legal research with a legislative approach that examines the Criminal Code, especially the crime of family embezzlement. In addition, a conceptual approach is also used to determine the deviation of criminal law principles so that efforts are obtained to overcome deviations from criminal law principles. This study concludes that there is a deviation of criminal law principles in the crime of embezzlement of joint assets committed by a husband or wife during marriage. This deviation is based on the inconsistency between the formulation of the crime which states that it cannot be prosecuted with the principle of criminal responsibility which regulates the reasons for eliminating the crime, namely the reason for forgiveness and the reason for justification. Furthermore, moral norms cannot prevent the prosecution of a criminal act, as long as there is a complaint from the victim as the concept of the complaint crime. Therefore, as a repressive effort in providing legal protection for victims, a formulation policy is needed by criminalizing embezzlement of joint assets committed by a husband or wife during marriage by eliminating the phrase